Impact of germination conditions on antioxidant properties and protein content in lentils (Lens culinaris) of Ukrainian cultivars - Yasinska, Iryna; Ivanova, Victoria (My University, 2018)
Changes in the free radical scavenging activity, the yield of phenolic compounds, ascorbic acid and proteins content in lentil seeds of two Ukrainian cultivars were determined during the germination period under different light conditions. Our results demonstrate that germinated lentil seeds both cultivars have advantages over non-germinated and can be useful in functional food technologies.
Keywords: кафедра технології оздоровчих продуктів; lentil; germination; antioxidant; protein; light; сочевиця; пророщування; антиоксиданти; білок; освітлення